Analysis of three-dimensional facet joint displacement during two passive upper cervical mobilizations. (December 2020) - Siccardi, Davide; Buzzatti, Luca; Marini, Michele; Cattrysse, Erik
Abstract: Background: Understanding the 3D-kinematics of the upper cervical spine during manual mobilization is essential for clinical examination and therapy. Some information about rotational motion is available in literature but translational components are often ignored, complicating the understanding of the complex inter-segmental motions. Objectives: This study aims to describe the amount, trajectories and reproducibility of atlanto-occipital facet joints' displacement during a flexion-extension mobilization and of the atlanto-axial facet joints during an axial rotation mobilization. Design: Original research using quantitative data. Methods: 20 fresh frozen human cervical specimens were examined with a Zebris® CMS20 ultrasound-based motion tracking system. Two physiotherapists performed regionalmobilizations in flexion-extension and axial rotation. The amount of displacement and the trajectories were calculated along the XYZ axes. Difference between measurements was evaluated with the Friedman two-way ANOVA test. Intra- and inter-rater reliability were estimated through ICC scores. Results: 3D-displacement (2.6–23.4 mm) was larger at C1–C2 during axial rotation, Atlanto-occipital flexion displayed the greatest variability in the C0 trajectory. During a right rotation, the left C1 facet moved mainly forward, and the right C1 facet moved backward. During a left rotation, the left C1 facet moved backward, while the right C1 facet moved forward. Intra-tester and Inter-tester ICCs varied between 0.5 and 0.90 (p < 0.005). Conclusions: During passive spinal motion, there is an important variability in magnitude and trajectory of joints' displacement. Nevertheless, different clinicians may be able to achieve the same position at the end of the mobilization. Highlights: Important difference in displacement between left and right joint. Greatest variability in joint trajectory during flexion-extension. Intra-tester ICC 0.60–0.80 for flexion-extension, 0.73–0.90 for axial rotation. Inter-tester ICC 0.50–0.87 for flexion-extension, 0.55–0.70 for axial rotation.